Membangun Kepribadian Anak dengan Dongeng - Vera Sophya, Ida (THUFULA, 2014)
Today, we can see that the negligence of parents and early childhood’steachers could not keep pace with the times. This can be seen from thedevelopment of increasingly sophisticated technology and the rise of children’stelevision programs become more interested. Given this phenomenon, theparents and educators particularly in early childhood environment, shouldbe flashback while they are still at an early age. The existence of storytellingactivities tend to have waned since eroded by age and sophisticated era. Thoughkeep in mind that there are many benefits by giving a fairy tale to children.Children’s tales are very useful for being able to glue the relationship betweenparents and their children, as well as helping to optimize the development ofchildren’s psychological and emotional intelligence. The examples of fairy talesthat can be given to children is a tale of local knowledge that can be drawnfrom the local legends and the unique stories.